Effect of door-to-angioembolization time on mortality in pelvic fracture: Every hour of delay counts. Issue 5 (May 2018) - Matsushima, Kazuhide; Piccinini, Alice; Schellenberg, Morgan; Cheng, Vincent; Heindel, Patrick; Strumwasser, Aaron; Benjamin, Elizabeth; Inaba, Kenji; Demetriades, Demetrios
Abstract : INTRODUCTION: Angioembolization (AE) is widely used for hemorrhagic control in patients with pelvic fracture. The latest version of the Resources for Optimal Care of the Injured Patient issued by the American College of Surgeons Committee on Trauma requires interventional radiologists to be available within 30 minutes to perform an emergency AE. However, the impact of time-to-AE on patient outcomes remains unknown. We hypothesized that a longer time-to-AE would be significantly associated with increased mortality in patients with pelvic fracture. METHODS: This is a 2-year retrospective cohort study using the American College of Surgeons Trauma Quality Improvement Program database from January 2013 to December 2014. We included adult patients (age ≥ 18 years) with blunt pelvic fracture who underwent pelvic AE within 4 hours of hospital admission. Patients who required any hemorrhage control surgery for associated injuries within 4 hours were excluded. Hierarchical logistic regression was performed to evaluate the impact of time-to-AE on in-hospital and 24-hour mortality. RESULTS: A total of 181 patients were included for analysis. The median age was 54 years (interquartile range, 38–68) and 69.6% were male. The median injury severity score was 34 (interquartile range, 27–43). Overall in-hospital mortality rate was 21.0%. The median packed red blood cell transfusions within 4 and 24 hours after admission were 4 and 6 units, respectively. After adjusting for other covariates in a hierarchical logistic regression model, a longer time-to-pelvic AE was significantly associated with increased in-hospital mortality (odds ratio, 1.79 for each hour; 95% confidence interval, 1.11–2.91; p = 0.018). CONCLUSION: The current study showed an increased risk of in-hospital mortality related to a prolonged time-to-AE for hemorrhagic control following pelvic fractures. Our results suggest that all trauma centers should allocate resources to minimize delays in performing pelvic AE. LEVEL OF EVIDENCE: Therapeutic/care management, level IV.